2016
DOI: 10.18632/oncotarget.12625
|View full text |Cite
|
Sign up to set email alerts
|

The role of transcriptional coactivator TAZ in gliomas

Abstract: The transcriptional coactivator with PDZ-binding motif (TAZ) is one of the important downstream effectors of Hippo pathway. In this study, the potential implication of TAZ in gliomagenesis was explored. TAZ expression was identified to be upregulated in glioma specimens and positively correlated with tumor grade. Meanwhile, its expression in nucleus was increased more significantly with the ascending order of tumor grade. Knocking down TAZ inhibited glioma cell proliferation, invasion and promoted apoptosis. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…To identify methods of inhibiting GBM growth, we carried out a small molecule screen using a library containing 1650 compounds, most of which are FDA-approved drugs. Our screen used LN229 human GBM cell line, which shows increased expression of TAZ 19 , presumably due to gene amplification (TCGA database). We confirmed that TAZ is essential for cell growth and tumorigenesis of LN229 cells by shRNA-mediated knockdown of TAZ in these cells (Figure S1A-S1F).…”
Section: Resultsmentioning
confidence: 99%
“…To identify methods of inhibiting GBM growth, we carried out a small molecule screen using a library containing 1650 compounds, most of which are FDA-approved drugs. Our screen used LN229 human GBM cell line, which shows increased expression of TAZ 19 , presumably due to gene amplification (TCGA database). We confirmed that TAZ is essential for cell growth and tumorigenesis of LN229 cells by shRNA-mediated knockdown of TAZ in these cells (Figure S1A-S1F).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, YAP/TAZ and β-catenin/TCF/LEF have been shown to work together in regulating target gene induction in the developing heart [48]. Although this has not been demonstrated in brain cancer, YAP and TAZ are frequently upregulated in glioma [49,50], and studies have shown that TAZ is required for the FZD7-induced proliferation of glioma cells [51], while TAZ inhibition leads to senescence and growth arrest [52].…”
Section: Discussionmentioning
confidence: 99%
“…The anti‐apoptotic molecule Bcl‐2 regulates the differentiation, activation, and survival of both osteoblasts and osteoclasts (Nagase et al, ). Expression of Bcl‐2 varied proportionally with the level of TAZ in glioma cells (Li et al, ). Induced overexpression of TAZ was able to increase Bcl‐2 expression and decrease expression of the Bcl‐2 associated X protein (Wang et al, ).…”
Section: Hippo‐pathway Genes Regulate Osteoclast Apoptosismentioning
confidence: 99%